Ragamuffin kid the boy without a smile : a story based on Juan Luna's painting Ragamuffin - Chong, Grace Dacanay; Taguiwalo, Beaulah Pedregosa; Luna, Juan Novicio 1857-1899. ([Makati City] Ayala Foundation, 2004)
Ragamuffin kid is a story of a lost boy named Bulan yearning for a love that is often taken for granted--love from one's own family.
Keywords: Orphans -- Philippines -- Ilocos Norte -- Juvenile fiction; Family -- Philippines -- Ilocos Norte -- Juvenile fiction; Philippine fiction (English)